2018
DOI: 10.1093/nar/gky446
|View full text |Cite
|
Sign up to set email alerts
|

The polyadenosine RNA-binding protein ZC3H14 interacts with the THO complex and coordinately regulates the processing of neuronal transcripts

Abstract: The polyadenosine RNA-binding protein ZC3H14 is important in RNA processing. Although ZC3H14 is ubiquitously expressed, mutation of the ZC3H14 gene causes a non-syndromic form of intellectual disability. Here, we examine the function of ZC3H14 in the brain by identifying ZC3H14-interacting proteins using unbiased mass spectrometry. Through this analysis, we identified physical interactions between ZC3H14 and multiple RNA processing factors. Notably, proteins that comprise the THO complex were amongst the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 74 publications
1
46
1
Order By: Relevance
“…3C). These ZC3H14 isoforms are primarily localized to the nucleus but can be detected in the cytoplasm of neurons (Bienkowski et al, 2017; Guthrie et al, 2011; Hector et al, 2002; Morris & Corbett, 2018). As shown in Figure 3A (Δ 13/ Δ 13 +Iso1 and Δ 13/ Δ 13 +Iso3), exogenous expression of either ZC3H14 Iso1 or ZC3H14 Iso3 appears to rescue dendritic spine density, which is confirmed through a semi-automated quantitative analysis of dendritic spine density [Δ 13/ Δ 13 (+Iso1) p <0.01; Δ 13/ Δ 13 (+Iso3) p <0.02] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3C). These ZC3H14 isoforms are primarily localized to the nucleus but can be detected in the cytoplasm of neurons (Bienkowski et al, 2017; Guthrie et al, 2011; Hector et al, 2002; Morris & Corbett, 2018). As shown in Figure 3A (Δ 13/ Δ 13 +Iso1 and Δ 13/ Δ 13 +Iso3), exogenous expression of either ZC3H14 Iso1 or ZC3H14 Iso3 appears to rescue dendritic spine density, which is confirmed through a semi-automated quantitative analysis of dendritic spine density [Δ 13/ Δ 13 (+Iso1) p <0.01; Δ 13/ Δ 13 (+Iso3) p <0.02] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that there is a pool of ZC3H14 present in the cytoplasm of neurons (Bienkowski et al, 2017; Morris & Corbett, 2018). To determine whether ZC3H14 is present in synaptosomes, which contain postsynaptic dendritic spines and presynaptic terminals (Chicurel, Terrian, & Potter, 1993), fractionation was performed as illustrated in Figure 7A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yra1‐Pcf11 interaction is conserved from yeast to humans, and has been suggested to modulate the assembly of the 3′‐end processing machinery . Recent work also shows that human THO interacts with the poly(A) RNA binding protein ZC3H14, and their interaction is required for proper control of bulk poly(A) tail length . Together, this multitude of connections between TREX and pre‐mRNA processing steps suggests that decision‐making during mRNA export is concurrent with pre‐mRNA processing.…”
Section: Assembly Of Export‐competent Mrnpmentioning
confidence: 98%
“…59,60 Recent work also shows that human THO interacts with the poly(A) RNA binding protein ZC3H14, and their interaction is required for proper control of bulk poly(A) tail length. 61 Together, this multitude of connections between TREX and pre-mRNA processing steps suggests that decision-making during mRNA export is concurrent with pre-mRNA processing. These connections may direct, step by step, the ATPase-powered remodeling reactions to ultimately mark mature transcripts with the export receptor, thereby ensuring the fidelity of gene expression specifically at the stage of mRNP nuclear maturation.…”
Section: Integration Of Pre-mrna Processing and Nuclear Mrnp Remodementioning
confidence: 99%